Penatalaksanaan Fisioterapi dengan IR, TENS, dan Latihan Pasca-ORIF Fraktur Tibia Distal di RS Soedjono Magelang - Dwi Septiyaningsih; Rima Yunitasari; Zuyina Luklukaningsih (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Background: ORIF is a surgical procedure involving internal fixation performed in fractures that cannot be healed manually or when a cast is unable to maintain the correct position of the bone fragments. After an ORIF procedure, patients will experience pain, swelling, limited mobility, and joint stiffness, so physiotherapy plays a crucial role in supporting the recovery process. Data show that of 111 fracture cases, 86 (77.5%) were treated with ORIF. Purpose of the Study: The purpose of this study was to determine and describe the physiotherapy management and clinical outcomes in cases of Post Orif Tibia 1/3 Distal with Infrared (IR), Transcutaneous Electrical Nerve Stimulation (TENS) and Exercise Therapy modalities at Dr. Soedjono Class II Hospital Magelang. Methods: This case study involved a 50-year-old male patient with a Post Orif Tibia 1/3 Distal case condition which was performed from December 2025 to January 2026 and. Results: The results of the study after 6 interventions showed a decrease in pressure pain from a scale of 4 to 2 and pain when moving from a scale of 6 to 2. Increased muscle strength in dorsiflexion movements from 4 to 5, plantar flexion movements from 4 to 5, and inversion movements from 4 to 5. Increased range of motion in the left ankle area in the sagittal plane from T0=12°-0°-20° to T6=20°-0°-35°, in the frontal plane T0=10°-0°-15° to T6=20°-0°-35° As well as an increase in functional activity T0=51,9% (moderate difficulty) to T6=80,7% (severe difficulties).